Caspase-1 in Cx3cr1-expressing cells drives an IL-18-dependent T cell response that promotes parasite control during acute Toxoplasma gondii infection. - Isaac W Babcock; Lydia A Sibley; Sydney A Labuzan; Maureen N Cowan; Ish Sethi; Seblework Alemu; Abigail G Kelly; Michael A Kovacs; John R Lukens; Tajie H Harris (PLoS Pathogens)
Inflammasome activation is a robust innate immune mechanism that promotes inflammatory responses through the release of alarmins and leaderless cytokines, including IL-1α, IL-1β, and IL-18. Various stimuli, including infectious agents and cellular stress, cause inflammasomes to assemble and activate caspase-1. Then, caspase-1 cleaves targets that lead to pore formation and leaderless cytokine activation and release. Toxoplasma gondii has been shown to promote inflammasome formation, but the cell types utilizing caspase-1 and the downstream effects on immunological outcomes during acute in vivo infection have not been explored. Here, using knockout mice, we examine the role of caspase-1 responses during acute T. gondii infection globally and in Cx3cr1-positive populations. We provide in vivo evidence that caspase-1 expression is critical for, IL-18 release, optimal interferon-γ (IFN-γ) production, monocyte and neutrophil recruitment to the site of infection, and parasite control. Specifically, we find that caspase-1 expression in Cx3cr1-positive cells drives IL-18 release, which potentiates CD4+ T cell IFN-γ production and parasite control. Notably, our Cx3cr1-Casp1 knockouts exhibited a selective T cell defect, mirroring the phenotype observed in Il18 knockouts. In further support of this finding, treatment of Cx3cr1-Casp1 knockout mice with recombinant IL-18 restored CD4+ T cell IFN-γ responses and parasite control. Additionally, we show that neutrophil recruitment is dependent on IL-1 receptor accessory protein (IL-1RAP) signaling but is dispensable for parasite control. Overall, these experiments highlight the multifaceted role of caspase-1 in multiple cell populations contributing to specific pathways that collectively contribute to caspase-1 dependent immunity to T. gondii.